The complete mitochondrial genome of sponge Halichondria okadai (Demospongiae, Suberitida, Halichondriidae) from Korea water. Issue 2 (20th December 2017) - Kim, Hana; Kim, Hyung June; Jung, Yun Hwan; Yu, Cheol; An, Yong Rock; Han, Donguk; Kang, Dong Won
Abstract: The mitogenome sequence of Sponge Halichondria okadai (Kadota, 1922) (Suberitida, Halichondriidae) was determined for the first time in this study. The circular genome is 20, 722 bp in length, containing 14 protein coding genes (PCGs), two ribosomal RNAs (rRNAs), and 25 transfer RNAs (tRNAs). The nucleotide composition of mitogenome consists of 29.5% A, 14.2% C, 21.5% G, 34.7% T, showing a high content of A + T similar to the other Suberitid sponges. These results will be useful for inferring the phylogenetic relationships among the members of family Halichondriidae within the Suberitids.